RANGKUMAN dan pengayaan bahasa Inggris kelas II SD semester 2 / Margareta Yulianti...[et.al] ; editor, Maria Agustina S, Flora Maharani ; ilustrator, Hernawan - Margareta Yulianti; Maria Agustina S; Flora Maharani; Hernawan (Kanisius, 2016)
93 hlm. : ilus. ; 25 cm.